Short-term Calorie Restriction and 17α-Estradiol Administration Elicit Divergent Effects on Proteostatic Processes and Protein Content in Metabolically Active Tissues. (10th May 2019) - Miller, Benjamin F; Pharaoh, Gavin A; Hamilton, Karyn L; Peelor, Fredrick F; Kirkland, James L; Freeman, Willard M; Mann, Shivani N; Kinter, Michael; Price, John C; Stout, Michael B
Abstract: 17α-Estradiol (17α-E2) is a "non-feminizing" estrogen that extends life span in male, but not female, mice. We recently reported that 17α-E2 had robust beneficial effects on metabolic and inflammatory parameters in aged male mice. However, it remains unclear if 17α-E2 also delays other "hallmarks" of aging, particularly maintaining proteostasis. Here, we used isotope labeling methods in older mice to examine proteostatic mechanisms. We compared weight-matched mild calorie restricted (CR) and 17α-E2 treated male mice with the hypothesis that 17α-E2 would increase protein synthesis for somatic maintenance. 17α-E2 had no effect on protein synthesis or DNA synthesis in multiple tissues, including white adipose tissue. Conversely, mild short-term CR decreased DNA synthesis and increased the protein to DNA synthesis ratio in multiple tissues. Examination of individual protein synthesis and content did not differentiate treatments, although it provided insight into the regulation of protein content between tissues. Contrary to our hypothesis, we did not see the predicted differences in protein to DNA synthesis following 17α-E2 treatment. However, mild short-term CR elicited differences consistent with both lifelong CR and other treatments that curtail aging processes. These data indicated that despite similar maintenance of body mass, 17α-E2 and CR treatments elicit distinctly different proteostatic outcomes.